Needs Analysis of Development of Critical Thinking Skills Assessment Instruments on Vocational School English Subjects - Ryzka Cahyaningrum; Wahyu Lestari; Supriyadi Supriyadi (Yayasan Visi Intan Permata, 2022)
This study aimed to analyze the needs for developing critical thinking skills technology-based assessment instruments in English subjects for vocational school and find out the factors that can support and inhibit developing and implementing critical thinking skills technology-based assessment instruments. This study used the qualitative research method with a case study design. The subject of study was 5 teachers and 15 eleventh-grade vocational school students at Tangerang. Observations, interviews, and documentation were conducted to collect the data. After collecting the data, the researcher used triangulation to confirm the data. The data collected were analyzed to answer the research questions using several stages, namely condensation, display, and verification. The results showed that the development of technology-based assessment instruments of critical thinking skills on vocational school English subjects needs to be developed. The schools have facilitation for conducting a technology-based assessment. Students have never taken on critical thinking skills assessment. Teachers and schools did not have the development of assessment instruments of critical thinking skills so teachers have never conducted critical thinking skills assessments on English subjects. Moreover, the students still have some obstacles in English learning such as vocabulary, pronunciation, and grammar. Therefore, the teachers should help to improve students’ vocabulary, pronunciation, and grammar before conducting a critical thinking skills assessment.